Virulence control in group A Streptococcus by a two-component gene regulatory system: Global expression profiling and in vivo infection modeling - Graham, Morag R. (The National Academy of Sciences, 2002)
Two-component gene regulatory systems composed of a membrane-bound sensor and cytoplasmic response regulator are important mechanisms used by bacteria to sense and respond to environmental stimuli. Group A Streptococcus, the causative agent of mild infections and life-threatening invasive diseases, produces many virulence factors that promote survival in humans. A two-component regulatory system, designated covRS (cov, control of virulence; csrRS), negatively controls expression of five proven or putative virulence factors (capsule, cysteine protease, streptokinase, streptolysin S, and streptodornase). Inactivation of covRS results in enhanced virulence in mouse models of invasive disease. Using DNA microarrays and quantitative RT-PCR, we found that CovR influences transcription of 15% (n = 271) of all chromosomal genes, including many that encode surface and secreted proteins mediating host–pathogen interactions. CovR also plays a central role in gene regulatory networks by influencing expression of genes encoding transcriptional regulators, including other two-component systems. Differential transcription of genes influenced by covR also was identified in mouse soft-tissue infection. This analysis provides a genome-scale overview of a virulence gene network in an important human pathogen and adds insight into the molecular mechanisms used by group A Streptococcus to interact with the host, promote survival, and cause disease.